Evaluation Method for Pitting Failure of the Planetary Gear System Under Impact Conditions - Fu Bowei; Yang Jie; Liu Yinghui; Feng Guojin; Zhen Dong (Jixie chuandong)
As the key structure of industrial reducers, the planetary gear system will be subject to cyclic load and impact load during the operation, which will cause metal fatigue peeling off the surface of gears and form pitting fault. When the system is subject to the impact load, the severe fluctuation of vibration signal will disturb the fault identification of the system. To solve this problem, a diagnostic index is developed based on the dynamic characteristics analysis of the planetary gear system with pitting fault under impact conditions. Firstly, the contact stiffness model of gear pairs is established based on the analytic geometry method and the Hertz contact theory. Secondly, the impact load is introduced, and the contact force between sun gears and planet gears is solved by the impact function method. Finally, based on the spectrum distribution of the system dynamic response signal, the energy index of the sideband centroid is proposed, which realizes the accurate identification of the fault impact and the load impact.